Reliability and sensitivity of the power push-up test for upper-body strength and power in 6-15-year-old male athletes - Gillen, Z. M.; Miramonti, A. A.; McKay, B. D.; Jenkins, N. D. M.; Leutzinger, T. J.; Cramer, J. T. (The Journal of Strength and Conditioning Research, 2018)
The power push-up (PPU) test is an explosive upper-body test performed on a force plate and is currently being used in high school football combines throughout the United States. The purpose of this study was to quantify the reliability of the PPU test based on age and starting position (knees vs. toes) in young athletes. Sixty-eight boys (mean ± SD; age = 10.8 ± 2.0 years) were tested twice over 5 days. Boys were separated by age as 6-9 years (n = 16), 10-11 years (n = 26), and 12-15 years (n = 26). The PPU test was performed on a force plate while rotating from the knees vs. the toes. Measurements were peak force (PF, N), peak rate of force development (pRFD, N/s), average power (AP, W), and peak power (PP, W). Intraclass correlation coefficients (ICC2,1), SEMs, coefficients of variation (CVs), and minimum detectable changes (MDCs) were calculated to quantify reliability and sensitivity. Peak force from the knees in 10-15-year-olds, PF from the toes in 12-15-year-olds, and pRFD from the knees and toes in 12-15-year-olds were comparably reliable (ICC = 0.84). Neither power measurements (AP or PP) for any age group, nor any measurements (PF, pRFD, AP, or PP) for the 6-9-year-olds were comparably reliable (ICC = 0.74). When considering the reliable variables, PF was greater in the 12-15-year-olds than in 10-11-year-olds (p = 0.05). In addition, in 12-15-year-olds, PF and pRFD were greater from the knees than from the toes (p = 0.05). For reasons largely attributable to growth and development, the PPU test may be a reliable (ICC = 0.80) and sensitive (CV = 19%) measure of upper-body strength (PF), whereas pRFD was also reliable (ICC = 0.80), but less sensitive (CV = 30-38%) in 10-15-year-old male athletes.